Math, asked by 8966804851harsh, 6 months ago

Sin A-CosA+1
sinA+ CosA-1
SECA -tan A​

Answers

Answered by manjeet464
0

Step-by-step explanation:

sin(a)−cos(a)+1

=

cos(a)

1

cos(a)

sin(a)

1

\frac{ \sin(a) \ - cos(a) + 1 }{ \sin(a) + \cos(a) - 1 } = \frac{ \ \cos(a) }{1 - \sin(a) }

sin(a)+cos(a)−1

sin(a) −cos(a)+1

=

1−sin(a)

cos(a)

(1 - \sin(a) )( \sin(a ) - \cos(a) + 1 ) = \cos(a) ( \sin(a) + \cos(a) - 1)(1−sin(a))(sin(a)−cos(a)+1)=cos(a)(sin(a)+cos(a)−1)

sinA - cosA +1 - sin²A -sinA cos A - sinA = sin A cos A + cos²A - cos A

1 - sin² A = cos ² A

sin²A + cos²A = 1

1=1 ( sin²A + cos²A is always equal to 1 this is an identity)

LHS = RHS

HENCE PROVED

Similar questions